Medical Students Show Lower Physical Activity Levels and Higher Anxiety Than Physical Education Students: A Cross-Sectional Study During the COVID-19 Pandemic - Souza, Karla Cardoso de; Mendes, Tassia Barcelos; Gomes, Tabatah Hellen Santos; Silva, Ariana Aline da; Nali, Luiz Henrique da Silva; Bachi, Andre Luis Lacerda; Rossi, Fabricio Eduardo; Gil, Saulo; França, Carolina Nunes; Neves, Lucas Melo (Frontiers in Psychiatry, 2021)
Objective: This study aimed to compare the time in physical activity (PA) [light (LPA), moderate and vigorous (MVPA)] and sedentary behavior (SB) (weekdays, weekends, or both) between Medical (MED) and Physical Education (PE) students who underwent remote classes imposed by the COVID-19. In addition, we compared symptoms of depression and anxiety and sleep quality. Methods: A cross-sectional study (272 MED and 95 PE students). The International Physical Activity Questionnaire (IPAQ), Beck Inventory (Anxiety, Depression), and Pittsburgh Sleep Quality were used to assess PA and SB, anxiety and depression symptoms, and quality of sleep, respectively. The data are presented as median and interquartile intervals 25–75. Results: We observed statistically significant differences between MED and PE students for MVPA [MED: 165 min per week (0–360) vs. PE: 420 min per week (180–670), p < 0.001], SB Total [MED: 10 h per day (8–12) vs. PE: 7 h per day (5–10), p < 0.001)], and anxiety symptoms [MED: 13 points (5–23) vs. PE: six points (2–16), p < 0.001)]. Conclusion: Together, our findings indicate that MED students spent less time in MVPA and more time in SB than PE students. MED students also presented worse mental health in the pandemic situation imposed by the COVID-19.